Democratization in Azerbaijan : the role of elections in holding on to power - Saatov, Rahim (2008)
The aim of this Master’s thesis is to investigate why the transition to democracy has failed in Azerbaijan as argued by some observers. The focus of the study is directed to the conduct of elections that were held in Azerbaijan between 1993 and 2003, under President Heydar Aliyev. The theoretical framework of this study is constructed on academic debate in the field of democratization among different scholars. Concepts, such as democracy and political power, have been used to provide a conceptual framework for this study. This study is a qualitative research with mainly secondary data. The primary source of the secondary data for the study was OSCE/UN and OSCE/ODIHR election observation mission reports, on three elections held in Azerbaijan between 1993 and 2003. The three elections were the 1995 parliamentary election, the 1998 presidential election and the 2003 presidential election. The reports were the OSCE/UN joint election observation mission report on the Parliamentary Election and Constitutional Referendum held on 12 November 1995; OSCE/ODIHR election observation mission report on the Presidential Election held on 11 October 1998; and the OSCE/ODIHR election observation mission report on the Presidential Election held on 15 October 2003. Additionally, secondary data for this study was collected from other international organizations’ reports, books, journal articles, conference papers, online newspapers, expert opinions, speeches and interviews of key Azerbaijani politicians, published in different Azerbaijani and international media outlets. The data was analyzed through narrative analysis to find out why the transition to democracy has failed in Azerbaijan. This was done by extracting and analyzing relevant information from the data which justifies why the transition to democracy has failed in the country. The findings revealed that the transition to democracy has failed in Azerbaijan as argued by some observers because the constitution and elections held in the country have been manipulated in favor of the ruling party led by President Heydar Aliyev. Thus, the study concluded that the lack of political will to promote democracy in Azerbaijan was the reason why the transition to democracy has failed in the country.